Analisis Hasil Uji Tarik Baja Karbon Penampang Silindris dan Segiempat - Dwi Angga Pramana Achmaddillah; Syamsul Hadi; Kreshna Aji Nursyifa; Agil Saputra Nugroho; Muhammad Hamdi Reynard Fahrezi; Gathan Atallah Farras Maulana (Konstruksi: Publikasi Ilmu Teknik, Perencanaan Tata Ruang dan Teknik Sipil, 2026)
The unknown exact tensile strength of cylindrical cross-section carbon steel and rectangular cross-section carbon steel is a problem faced. The purpose of the research is to obtain the tensile strength of cylindrical cross-section carbon steel and rectangular cross-section carbon steel. The research method is carried out by turning carbon steel specimens to a diameter of 7.92mm, a length of 200mm and milling carbon steel cross-sections with a width of 12mm, a thickness of 4mm, setting the Tarno Grocky tensile testing machine, clamping both ends of the specimen with grips, tensile testing until the specimen breaks, measuring the gauge length after the specimen breaks and is properly cupped again, making stress and strain curves, and analyzing the tensile test results. The test results show that the tensile strength of carbon steel with a cylindrical cross-section is 554 MPa at a strain of 3.86%, the yield strength is 514 MPa at a strain of 3.06% and the tensile strength of carbon steel with a rectangular cross-section is 712 MPa at a strain of 2.45% and the yield strength is 487 MPa at a strain of 0.59%, which implies that both steels are ductilely broken, due to shrinkage. cross-section (necking) which includes ST 60 because the yield strength is more than 360 MPa.